Worship time: the journey towards the sacred and the contemporary Christian charismatic movement in England - Elliott, Esther (1999)
This thesis is an ethnographic description of the Charismatic movement in England as it is to be found in the mainstream denominations. It specifically focuses on the Baptist denomination and uses the life and faith of the Jesus Fellowship Church as a controlling example of a Charismatic group which sits on the boundaries of both denominational and Baptist life. It traces the history, social organisation and framework of understanding of the movement and then highlights the Charismatic practice known as a worship time. It argues that in worship Charismatics become individual axis mundi, or channels for the transitory presence of the sacred on earth. This thesis also traces evidence which suggests that Charismatics represent this transitoriness in their use of physical space to delineate the sacred. They base their use of this space around a model by which they also construct the shape of the universe and organise their social relationships. In the activity conducted in this sacred space Charismatics journey towards the sacred through the use of music, words and ideas which are built into a flow of feeling that moves towards a goal. This ethnographic description is based on the theoretical and methodological programme of cultural anthropologists such as Turner, Bell and Geertz who have emphasised the idea of ritual as a functional process and, in the case of the latter two, the creation of meaning by which to live as a fundamental basis for all social and cultural life. It does so in direct response to other understandings of the Charismatic movement which focus on issues of power and forms of social relationships by using a different theoretical and methodological programme.